Citation practices in EFL academic writing: The use of reporting verbs in Masterâ€™s thesis literature reviews - JarkovskÃ¡, Martina; KuÄÃrkovÃ¡, Lenka (Universitas Pendidikan Indonesia, 2020)
Reporting belongs among key features of academic writing, and reporting verbs (RVs) are probably the most explicit way of attributing the content to other sources.Â For EFL learners, the correct use of RVs is often challenging. While most EFL studies focus on the functions of citation as used by novice researchers in research articles, Ph.D. theses, or university writing, fewer works are concerned with Master's theses, often students' first encounter with original scientific and academic writing. This study explores the use of RVs in EFL learners' Master's theses. Besides investigating the types and functions of RVs, the choices of the verb tense, voice, and the subject-agent in the reporting structures are explored. The research was performed on 82 Master's thesis Literature Reviews written in English by Czech economics and management students. To determine the types and functions of RVs, the study adopts Hyland's (1999, 2002) framework. First, the frequencies of RVs occurrence are counted, and RVs are discussed in terms of process categories and evaluative functions. Second, the choices of the verb tense, voice, and the subject-agent in the reporting structures are analysed. The findings show a predominant use of RVs conveying a neutral attitude towards the reported content and neutrally summarizing the previous research in the present simple active tense with named-author as the subject. Although the results confirm the trend common for novice researchers and soft discipline writers, we believe that the enhancement of appropriate use of RVs in academic writing courses is necessary. The findings might offer insights applicable to EFL contexts and contribute to the body of existing research on the citation.